Promoting literacy and lettering: the transforming potential and the influence of erudite music in the creative process of literary production of authority - Souza, Silvana Lemes de; Gualda, Linda Catarina (Revista Hipótese, 2019)
Considering the high percentage of Elementary and High school students that present below the skills and abilities necessary for the series in which they are, the article shows an experimental research applied at a state school in the interior of the state of São Paulo. It was tried to demonstrate the influence of erudite music as a stimulus in the creative process of literary texts. The test was applied in 2 groups: one experimental and the other control. Although unexpected results emerged, the aim of the work was achieved, demonstrating that classical music was the differential in the process of producing literary texts.